A novel approach for near-surface defect detection in FRP-bonded concrete systems using laser reflection and acoustic-laser techniques. (15th June 2017) - Qiu, Qiwen; Lau, Denvid
Graphical abstract: Highlights: Laser reflection technique can recognize the defects in FRP-bonded concrete system. Laser reflection technique can provide an instant and economical defect detection. Defect size can be accurately quantified by the acoustic-laser technique. A combined use of laser reflection and acoustic-laser technique is proposed. Abstract: Two different methods ( i.e. laser reflection and acoustic-laser techniques) for defect detection in fiber-reinforced polymer bonded concrete systems are studied. Both the simulation and experimental results demonstrate that laser reflection technique can instantly and economically identify the presence of defect but cannot quantify the defect size. In contrast, acoustic-laser technique is more sophisticated to be used and it enables a reliable measurement of the defect size. A new and economical detection scheme combining these two techniques is established so that a single or multiple defect region can be rapidly recognized by laser reflection technique and the defect size can be predicted by acoustic-laser technique.